A prática do stand-up paddle nas aulas de educação física: uma estratégia para educação ambiental - (:unkn) unknown (Universidade Brasil, 2021)
The search for the practice of adventure sports has gained popularity among young people and the general population, having seen the insertion of adventure mode in the Olympic games. Stand up Paddle is a practical modality with a board and a paddle, it can be performed in the sea, pools, ponds, rivers, and reservoirs. The objective of the study was to investigate the practice of StandUp Paddle in Physical Education classes as a strategy to raise the awareness of educators and students about the importance of preserving the environment. The research was developed through a qualitative approach, with bibliographic review on the theme in books, articles, dissertations, and theses. The final product was the construction of a Pedagogical Didactic Manual. It can be evidenced that the pedagogical didactic manual is an alternative to stimulate educators to have a greater interest on the environmental theme, motivation to elaborate other projects and other experiences and with that it allows all the participants to raise awareness about the importance of environmental preservation for the current and future generations. The work with Environmental Education is a proposal that needs to take root in the teaching systems, state and / or municipal, as a valuable curricular practice, during a critical and humanizing perspective, with the horizon of building a less unequal society, fairer and more sustainable.
Keywords: Educação ambiental; Preservação ambiental; Esportes a remo; Ensino fundamental; Educação crítica; CB